The central role of peers facilitators in the empowerment of breast cancer patients: a qualitative study - Béatrice Lognos; Isabelle Boulze-launay; Million Élodie; Gérard Bourrel; Michel Amouyal; Xavier Gocko; Clary Bernard; Grégory Ninot; Agnès Oude Engberink (BMC, 2022)
Abstract Background In 2020, the number of new cancer cases was estimated at 20 490 862 worldwide up from 18.1 million in 2018 and 14.1 million in 2012. Since the 2000s, cancer treatments have significantly improved, allowing either a cure or control of the disease. Patients share their experience of the disease and use supportive care solutions through involvement in patient associations and online forums. All the associations were built on the principle of "peer support," which is based on mutual aid between people who suffer or have suffered from the same somatic or psychological illness or had the same life experience. This experiential knowledge can be explored to understand the role of peers and associations in the appropriation of their cancer. Methods A qualitative phenomenological study was undertaken through semi-structured interviews with 12 participants. Interviews were audio-recorded, transcribed verbatim, then analyzed by means of triangulation up to the point of theoretical saturation by a semio-pragmatic method. Results Four categories emerged: (1) "Transforms a painful experience into a positive one. It mobilizes the human values of sharing, love, and humility, which facilitates resilience"; (2) "The characteristics of the association, a non-medical place between people sharing a common destiny, resonates with patients' needs and improves their well-being"; (3) "The association transforms the patients' experiences by facilitating engagement that leads to a patient-expert (empowerment)"; and (4) "Understanding what is happening to them is soothing, reassuring, because patients' concerns need to be heard and their care understood". Conclusions This study highlights patient associations can serve as the mediator of NPI and facilate the empowerment of breast cancer patients. Practice implications Educating health professionals in initial and continuing education about non-pharmacological interventions will be a major issue. Teaching the patient-centred approach to health professionals is one of the priorities in initial and continuing medical education.